1999
DOI: 10.1136/bmj.318.7193.1240
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorder and clinical care in people convicted of homicide: national clinical survey

Abstract: Objectives To estimate the rate of mental disorder in those convicted of homicide and to examine the social and clinical characteristics of those with a history of contact with psychiatric services. Design National clinical survey. Setting England and Wales. Subjects Eighteen month sample of people convicted of homicide. Main outcome measures Offence related and clinical information collected from psychiatric court reports on people convicted of homicide. Detailed clinical data collected on those with a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
2
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 8 publications
3
61
2
8
Order By: Relevance
“…Some authors have found that psychotic individuals are more likely to murder family members or close acquaintances, 16 whereas the murder of strangers are more frequently perpetrated by abusers of alcohol or drugs. 17 Simpson et al found that, in 74% of abnormal homicides, the victims were family members or partners of the perpetrators, compared with 9% in normal homicides.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have found that psychotic individuals are more likely to murder family members or close acquaintances, 16 whereas the murder of strangers are more frequently perpetrated by abusers of alcohol or drugs. 17 Simpson et al found that, in 74% of abnormal homicides, the victims were family members or partners of the perpetrators, compared with 9% in normal homicides.…”
mentioning
confidence: 99%
“…16 This group accounted for 70% of the convictions for murder during the study period. The authors found that 6% of these murders were committed by individuals with schizophrenia, and 44% were committed by individuals with a history of some type of mental disorder, although other diagnoses were not specified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No presente estudo, a hipótese de alguns autores que consideram possível efeito do álcool nos crimes violentos por pacientes psicóticos (e pela atividade delirante) não foi confirmada 11,15 . Certamente, o presente estudo tende a sugerir associação entre a psicopatologia do delírio e o ato violento, independentemente do uso do álcool ou da droga.…”
Section: Discussionunclassified
“…Estudos realizados em diferentes países (Estados Unidos, Inglaterra, Austrália e República Checa) com prisioneiros que tinham cometido crimes violentos indicaram prevalência mais elevada da esquizofrenia neste grupo (prisioneiros) em comparação com a população geral, não obstante as limitações das generalizações por causa dos vieses de tais estudos [8][9][10][11][12][13][14][15] . Outros estudos, entretanto, indicaram associação negativa entre psicose e violência.…”
Section: Artigo Originalunclassified